Supply Chain Strengthening Strategy For Micro-Enterprises Based On Community Units In Cimahi City - Sjamsuridjal Sjamsuridjal; Iman Sudirman; Ester Manik (International Journal of Social Sciences, 2026)
Strengthening the micro-enterprise supply chain still faces various obstacles, particularly unintegrated supply chain management, weak coordination among business actors, limited market access, and suboptimal stakeholder collaboration. Research on Supply Chain Management (SCM) in micro-enterprises generally continues to focus on operational aspects and logistics efficiency, while the integration of collaborative governance based on community-level-administrative units within supply chain management remains relatively limited. This study aims to develop a collaborative community units-based Supply Chain Management strategy as a strategic approach to support supply chain effectiveness for micro-enterprises. This study employs a qualitative approach with a single case study method focusing on the processed food micro-industry in Cimahi City. Data collection was carried out through in-depth interviews, observation, documentation, and focus group discussions (FGD) involving micro-enterprise actors, local government, community units, academics, and relevant stakeholders. Data analysis was conducted through data reduction, triangulation, strategic factor analysis, and the formulation of the micro-enterprise supply chain strategy. The results indicate that the primary supply chain issues for micro-enterprises include weak information integration, limited coordination among business actors, low technology utilization, and suboptimal multi-stakeholder collaboration. This research yields a supply chain effectiveness strategy for micro-enterprises based on the community units. The developed strategies include strengthening collaborative networks, information integration, capacity building for business actors, and strengthening partnerships among stakeholders. This study provides a theoretical contribution to the development of the concept of Community-Based Supply Chain Management within the context of micro-enterprises.